Induced film forming type concrete surface layer protection material and protection method thereof

By adding mineralizers and self-healing capsules to the concrete and applying induction layer solution and polydimethylsiloxane material to the surface to form a self-healing protective layer, the concrete surface protection material in the prior art is easily aged and the problem of limited penetration depth, efficient corrosion resistance and long-term durability are achieved.

CN119219361APending Publication Date: 2024-12-31ZHONGLU JIAOKE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411371556.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing concrete surface protective materials are prone to aging during long-term use and have limited penetration depth, making it difficult to effectively resist external erosion ions, resulting in reduced durability and shortened service life.

Method used

The surface protection method of induced film-forming concrete is adopted. By adding mineralizers and self-healing capsules to the concrete, and applying the induction layer solution and polydimethylsiloxane material to the surface, a self-healing protective layer is formed. When the surface layer is damaged or the pH changes, the self-healing capsule releases protective materials for repair, enhancing the concrete's corrosion resistance.

Benefits of technology

It significantly improves the resistance of concrete to external corrosion media, provides long-term durability protection, extends the service life of concrete, and reduces the cost of later repair and maintenance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of concrete protection, in particular to an induced film forming type concrete surface layer protection material and a protection method thereof.The protection method comprises the steps that a mineralizing agent and self-repairing capsules are added into concrete to be evenly mixed for use; coating the inducing layer solution on the surface of the template; the mixed concrete is poured into the formwork; and the surface of the poured concrete is coated with a polydimethylsiloxane material. The mineralizer is migrated from inside to outside under the action of an induction layer solution on the surface of the concrete formwork, mineralization and film formation are induced, the penetration depth can be increased, an erosion medium transmission channel can be filled, and meanwhile the interface bonding capacity with a hydrophobic layer can be improved through active groups in an induction layer; when the surface layer is damaged in service, the self-repairing capsule is influenced by pH, and the released protective material is migrated to the surface layer for repairing; the surface layer protection material can greatly improve the ability of the concrete to resist external erosion media, and provides repair when the surface layer protection fails, so that the long-acting durability of the concrete is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete protection, and in particular to an induced film-forming concrete surface protective material and a protective method thereof. Background Art

[0002] At present, concrete materials are widely used in facilities such as bridges, tunnels, ports, and dams. Due to factors such as design grade, construction control, and microscopic pore structure, concrete is easily affected by Cl in the external environment. - 、SO4 2- Plasma erosion, carbonization, and freeze-thaw damage cause varying degrees of damage, reduced durability, and shortened service life. Traditional methods add pore sealers and sealants to fill capillary channels, which seriously affects the workability and mechanical properties of concrete. Applying surface protective materials is a common method to protect concrete from corrosive ions.

[0003] Different types of surface protection materials have different mechanisms of action and effects. The epoxy putty, polymer mortar, penetrating crystalline materials, etc. of the base coat use the materials to solidify and bond while penetrating from the surface to the inner layer, but the penetration depth is limited and only seals the surface pores. If the surface is damaged and the protection fails, the corrosive ions will still enter the concrete and cause damage. Surface protective coatings are mostly polyurethane, epoxy resin, and acrylate organic materials. They are easily aged by long-term exposure to light radiation, high and low temperature alternation, etc. The protective layer is irreversible after failure and needs to be repaired and painted from time to time, which greatly increases the construction cost. In addition, the existing concrete is coated with hydrophobic impregnation materials such as silane and fluorosilane on the surface, which only provides super-hydrophobic or anti-pollution capabilities and cannot reduce the erosion of harmful ions.

[0004] In actual projects, primer, topcoat and hydrophobic impregnation materials are often used in combination to obtain a multi-layer protective structure to further extend the service life of concrete. However, there are still problems such as limited penetration depth of post-coating materials, poor interface bonding, and easy aging and failure.

[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0006] The first purpose of the present invention is to provide an induced film-forming concrete surface protection method. When the surface is damaged during service, the self-repairing capsule is affected by the pH value and releases protective materials to migrate to the surface for repair. The surface protective material can greatly enhance the ability of concrete to resist external corrosive media, and provide repairs when the surface protection fails, thereby ensuring the long-term durability of the concrete.

[0007] The above technical objectives of the present invention are achieved through the following technical solutions:

[0008] An induced film-forming concrete surface protection method comprises the following steps:

[0009] Add the mineralizer and self-repairing capsules into the concrete and mix them evenly for later use;

[0010] Applying the induction layer solution on the template surface;

[0011] Pour the mixed concrete into the formwork;

[0012] Polydimethylsiloxane material is applied on the concrete surface after pouring.

[0013] Furthermore, the mineralizer and self-repairing capsules are added to the concrete and mixed evenly for use; this means that the mineralizer is mixed with mixing water in advance, the self-repairing capsules are mixed with cement, and cement, sand, and gravel are added according to the concrete preparation ratio, and mixed evenly. The pre-mixing of the self-repairing capsules with cement dry materials can effectively protect the capsules from being damaged during the concrete mixing process. Compared with direct mixing with water or sand and gravel, this method reduces the possibility of mechanical damage to the capsules during the mixing process, ensures that the self-repairing capsules remain intact during the pouring process, prevents them from breaking in advance, and ensures that the self-repairing function plays a role in the service of the concrete.

[0014] Further preferably, the raw materials used for concrete are: cement is silicate cement, with a specific surface area of ​​≥300m 2 / kg, 28d compressive strength ≥42.5MPa; sand is river sand with continuous grading and particle size of 0.1-3mm; gravel is basalt gravel with continuous grading and particle size ranging from 10-25mm.

[0015] Further, the induction layer solution is applied to the surface of the formwork; it means that before pouring concrete, the formwork is set up, polished and cleaned, and the induction layer solution is applied at a rate of 0.1-0.5 kg / m 2 Apply the induction layer solution, let it stand for more than 2 hours, then pour the mixed concrete and vibrate it evenly. Let it stand for more than 2 hours after application to ensure that the induction layer solution is fully combined with the template to form an effective induction layer structure. This standing time allows the metal enzyme to form a stable bond with the template surface, providing more mineralization nucleation points and ensuring that the mineralization reaction proceeds evenly on the concrete surface.

[0016] Furthermore, polydimethylsiloxane material is applied to the surface of the poured concrete. After pouring, the concrete is left to stand for 24 hours. During the 24 hours, the concrete is hydrated and the pore structure is not fully formed. The induction layer solution can easily enter the pores. Then, the formwork is removed and the concrete surface is immediately coated with polydimethylsiloxane at a rate of 0.1-0.2 kg / m 2Spray polydimethylsiloxane material. Polydimethylsiloxane can form a hydrophobic protective film on the surface of concrete. This film can effectively block the penetration of water and reduce the damage of water, chloride ions and other corrosive media to concrete.

[0017] The second purpose of the present invention is to provide an induced film-forming concrete surface protective material, which can trigger a self-repairing function and restore its protective performance when the surface protection is damaged during the service of the concrete. The self-repairing capsule can rupture under the influence of pH changes inside the concrete, release protective materials, and migrate to the surface of the concrete for repair, thereby significantly improving the ability of the concrete to resist external corrosive media, and providing effective repair when the surface protection fails, ensuring the long-term durability of the concrete.

[0018] The above technical objectives of the present invention are achieved through the following technical solutions:

[0019] An induced film-forming concrete surface protective material is used in the above-mentioned induced film-forming concrete surface protective method, wherein the mass ratio of the mineralizer, the self-repairing capsule, the inducing layer solution and the polydimethylsiloxane is 10-20:10-20:20-40:20-40.

[0020] Among them, the metal enzymes in the induction layer solution can chelate mineralized cations and promote the combination of these cations with anions in the mineralizer to form crystalline minerals. This process gradually fills and closes the pores of the concrete from the inside out, enhancing the compactness and impermeability of the concrete. In addition, the post-placed polydimethylsiloxane material can form a strong bond with the active groups in the metal enzymes, further enhancing the protective properties of the surface layer. By matching this material with the internal admixture and formwork coating process of the concrete, the problem of reduced activity of the metal enzymes in a high pH environment and high metal cation concentration is avoided, while maintaining the role of its nucleation site to ensure the protective effect of the concrete. When the concrete surface is partially damaged or the protective material fails, the internal pH change will cause the capsule wall of the self-healing capsule to rupture, releasing the protective materials inside. These materials can migrate to the damaged area for effective repair and improve the long-term durability of the concrete.

[0021] Furthermore, the mineralizer is a CO3 2- and SiO3 2- Soluble salt solution with ion molar concentration of 0.01-2.0 mol / L. It is one or more of Na2CO3, K2CO3, Na2SiO3, K2SiO3 aqueous solution, which is added to concrete by mixing with mixing water, and the addition amount is 1%-5% of the concrete mass. The mineralizer can be evenly distributed in the concrete by mixing with mixing water. The addition ratio of 1%-5% ensures sufficient mineralization effect without negatively affecting the performance of concrete, such as fluidity or strength reduction.

[0022] Ca 2+ +CO3 2- →CaCO3;

[0023] Ca 2+ +SiO3 2- →CSH;

[0024] CaCO3 is the main filling material inside concrete, which can effectively block pores and reduce the chance of external corrosive media entering the concrete; CSH is one of the main products of cement hydration, which can give concrete high strength and low permeability, further improving its durability. These reactions gradually form mineral deposits inside the concrete, close the pores, and form a solid mineralized layer; because the mineralization reaction is gradual, this mineral filling process can increase the structural density of concrete from the inside, especially in the long-term service process, can enhance its anti-corrosion ability and durability.

[0025] Further preferably, the ion molar concentration is preferably 0.1-1.0 mol / L, in order to provide the required anions for inducing mineralization membrane, and the anion mineralizer solution with a specific concentration and dosage can be used to control the generation rate of mineralized products, the size of the crystalline particles of the mineralized products, and the layer structure and morphology of the mineralized products according to the concentration in combination with the thickness of the concrete molding.

[0026] Furthermore, the self-repairing capsule is composed of a capsule wall material and a capsule core material, and is spherical in shape with a diameter of 0.75 to 1.18 mm. The amount of addition is 1% to 5% of the mass of the concrete, and the amount of the self-repairing capsule is adjusted according to the depth per unit area of ​​the prepared concrete. The spherical capsule structure has good fluidity and dispersibility, making it easier for the self-repairing capsule to be evenly distributed in the concrete mixture. It can effectively fill pores of different depths and positions. The diameter of the capsule is set in the range of 0.75 to 1.18 mm, which not only ensures that the protective material content inside the capsule is sufficient, but also ensures that it can effectively rupture when the concrete surface is damaged or the pH changes, releasing the repair material therein for local repair.

[0027] Furthermore, the capsule wall material is a chitosan molecule; its chemical structure is shown as follows, wherein n is ≥1.

[0028]

[0029] Furthermore, the capsule core material is polydimethylsiloxane material. The molecular formula is (C2H6OSi)n, where n≥1, and its structural formula is as follows:

[0030]

[0031] Preferably, the self-repairing capsule provides a two-phase interface through an interfacial polycondensation method, and the capsule core and the capsule wall material undergo a polycondensation reaction, and the capsule core is embedded in the capsule wall material. The aqueous solution of the capsule wall material and the capsule core material are mixed in a mass ratio of 1:1, and the pH is adjusted to 3.5; the mixed solution is transferred into a jacketed bottle, and the reaction is carried out at a constant temperature of 60°C and a speed of 300r / min. The reaction is carried out for 2h. After the reaction is completed, the filter is filtered, and the filter cake is washed with water, and dried at 40°C for 24h to obtain a self-repairing capsule.

[0032] When concrete is corroded by external factors and the local pH value decreases (such as acidic conditions caused by carbonization), the amino groups of chitosan are protonated in the acidic environment, dissolving or structurally denaturing, causing the capsule wall to rupture. At this time, the capsule core material polydimethylsiloxane (PDMS) will be released and will quickly diffuse and fill the cracks. Through its silicon-oxygen bonds, it will chemically bond with the silicate components in the concrete matrix to form a stable protective layer, thereby restoring the waterproof and erosion resistance of the cracks and preventing further physical and chemical damage.

[0033] Furthermore, the induction layer solution is prepared by mixing the metal enzyme and the cationic solution in a mass ratio of 1: 1. The metal enzyme can effectively control the release rate of the cation by forming a stable coordination complex with the cation, prevent premature mineralization reaction, make the mineralization process uniform, improve the uniformity and density of the protective layer, and reduce the occurrence of local weak points.

[0034] Further, the metal enzyme is one or a combination of tyrosinase, glutaminase and histidase. All of them contain phenolic hydroxyl, carboxyl, amine and other groups. Tyrosinase can form a stable coordination bond with metal ions through its phenolic hydroxyl; glutaminase forms a coordination bond with metal ions through its carboxyl and amine groups; histidase forms a coordination bond with metal ions through its amino group and imidazole ring.

[0035] Preferably, the cationic solution is Ca 2+ Mg 2+ Soluble salt, the ion molar concentration of which is 0.02-2.0 mol / L. It is one or a combination of calcium chloride, calcium acetate, calcium lactate, calcium bromide, magnesium chloride, magnesium bromide, and magnesium sulfate, and the added amount is equal to that of the anion mineralizer.

[0036] Further preferably, the ion concentration is preferably 0.1-1.0 mol / L. In order to provide the required cations for inducing the mineralization membrane, the cationic mineralizer solution with a specific concentration and dosage can be combined with the thickness of the concrete molding to control the generation rate of the mineralized product, the size of the crystal particles of the mineralized product, and the layer structure and morphology of the mineralized product according to the concentration. At the same time, the electrostatic attraction generated when the concentration is too high will inhibit the activity of the enzyme.

[0037] In summary, the present invention has the following beneficial effects:

[0038] (1) The present invention provides an induced film-forming concrete surface protective material and a protective method. The metal enzyme in the induction layer solution can chelate mineralized cations, promote the formation of crystalline minerals with anions in the mineralizer, gradually fill and seal the concrete pores from the inside to the outside, and then apply a polydimethylsiloxane material to generate a strong bond with the active groups in the metal enzyme. The use process of matching the internal admixture and template coating can prevent the metal enzyme from being affected by the pH (11 to 13) of the concrete and the concentration of metal cations, resulting in reduced activity and loss of nucleation sites. When the concrete surface is partially damaged or the protective material fails, the internal pH changes, causing the self-repairing capsule wall to rupture, releasing the protective material to migrate to the surface for repair, thereby improving durability.

[0039] (2) The present invention provides an induction layer solution that reacts with a mineralizer to form a protective layer composed of mineralized crystals. The hydroxyl, amino, amide, carboxylic acid and other negative ion groups on the surface of the metal enzyme effectively bind cations from the environment. The biomass structure on the surface of the metal enzyme creates an affinity environment and pores for crystallization, which can serve as a heterogeneous nucleation site for mineral deposition, which is beneficial to crystal nucleation, growth and aggregation, and induces CO3 in the mineralizer to form a protective layer composed of mineralized crystals. 2- and SiO3 2- It gradually migrates to the surface, generating CaCO3, CaSiO3, MgCO3, and MgSiO3 crystalline particles, gradually reaching supersaturated deposition, forming a continuous phase that gradually fills the micro-nano pores on the surface of the concrete from the inside to the outside, forming a mineralized layer for surface protection.

[0040] (3) The induction layer solution provided by the present invention can provide good adhesion and chemical bonding for the subsequent coating. When the template is removed, the rich active groups on the surface of the metal enzyme in the induced mineralization layer are directly exposed to the outer surface to form a strong bond with the sprayed polydimethylsiloxane material, and the functional molecules of the generated mineralization layer are modified to generate a low surface energy layer on the concrete surface. Since the siloxane poly contains high molecular weight alkyl groups, it has high hydrophobicity and plays an anti-pollution role. At the same time, it enhances the bonding performance and improves the durability of the concrete surface protection.

[0041] (4) The self-repairing microcapsules provided by the present invention can improve the durability of concrete surface protection. When the concrete is partially damaged or the protective material fails, the external corrosive ions enter and cause the pH value inside the concrete to be less than 11. The protonation degree of the amino group of the capsule wall material chitosan is reduced, and the network structure connected by hydrogen bonds and electrostatic attraction is destroyed, so that the molecular chain is fully stretched, the mechanical strength of the capsule wall is reduced, swells, and ruptures, and the capsule core material is leached and migrated to the protective layer. When the internal pH is 11-13, the amino structure of the capsule wall material shrinks and stops releasing the protective material. It can provide long-term and durable surface protection for concrete. DETAILED DESCRIPTION

[0042] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the technical scheme proposed according to the present invention, its specific implementation method, characteristics and effects are described in detail as follows.

[0043] Sources of raw materials used in the embodiments and comparative examples:

[0044] Mineralizer: Contains CO3 2- and SiO3 2- Soluble salt solutions, including Na2CO3 (CAS: 497-19-8), K2CO3 (CAS: 584-08-7), Na2SiO3 (CAS: 1344-09-8), and K2SiO3 (CAS: 1312-76-1), were all purchased from MacLean's reagent.

[0045] Metalloenzymes: tyrosinase (CAS: 82310-93-8), glutaminase (CAS: 142-47-2), and histidase (CAS: 71-00-1) were purchased from Murdoch Chemicals.

[0046] Cationic solution: containing Ca 2+ Mg 2+ Soluble salts, including calcium chloride (CAS: 10043-52-4), calcium acetate (CAS: 62-54-4), calcium lactate (CAS: 814-80-2), calcium bromide (CAS: 17789-41-5), magnesium chloride (CAS: 7786-30-3), magnesium bromide (CAS: 7789-48-2), and magnesium sulfate (CAS: 22189-08-8), are all obtained from MacLean's reagent.

[0047] Capsule wall material: Chitosan, molecular formula is C6H 12 NO4; CAS: 9012-76-4, collected from Shanghai Aladdin Biochemical Technology.

[0048] Core material: polydimethylsiloxane, C8H 24 O2Si3, CAS: 107-51-7, from Merck Chemicals.

[0049] Concrete materials: Cement: P·O42.5 ordinary Portland cement, sourced from Conch Cement Plant, with a specific surface area of ​​328m 2 / kg, and the compressive strength at 28d is 47MPa.

[0050] Sand: river sand, Nanjing Kangshen Building Materials, particle size 0.1~3mm, continuous grading.

[0051] Gravel: Basalt gravel, Hebei Yueshan Environmental Protection Technology Co., Ltd., particle size range 10 ~ 25mm.

[0052] The use method of concrete surface protection material is based on performance. The hardened concrete uses standard specimen size to simulate the concrete protection performance of on-site support formwork. The induction layer solution is applied to the test mold, and the mold is removed after hardening for 24 hours. The polydimethylsiloxane material is sprayed again and cured for 28 days. The performance is evaluated as follows:

[0053] (1) Expansion: Refer to the Standard for Performance Test Methods of Ordinary Concrete Mixtures GB / T50080-2016, and test the expansion of the concrete after mixing and after standing for 10 minutes. The measurement should be accurate to 1 mm.

[0054] (2) Setting time: The setting time determination method in the Standard for Performance Test Methods of Ordinary Concrete Mixtures GB / T50080-2016 shall be used, with the measurement accuracy being 1 minute.

[0055] (3) Compressive strength: Refer to "Test Methods for Mechanical Properties of Concrete" GB / T50081-2019, the size of the molded specimen is 100*100*100mm, and the measurement accuracy is 1MPa; the low temperature of concrete curing is -5℃ and -20℃ respectively; according to the needs of emergency repair and reinforcement, the 24h strength needs to be measured.

[0056] (4) Carbonation depth: refer to the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete (GB / T50082), the specimen size is 100×100×300mm prism specimen, the CO2 concentration in the carbonation box is maintained at (20±3)%, and the carbonation depth d is measured with an accuracy of 1mm.

[0057] (5) Freeze-thaw resistance: "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T50082), the specimen size is 100×100×400mm, the mass loss is measured in %, and 100 cycles are considered as one cycle. The specimen size is 100×100×100mm, and the compressive strength is measured in MPa, and 200 cycles are considered as one cycle.

[0058] (6) Sulfate corrosion resistance coefficient: Referring to the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete (GB / T50082), the specimen size is a cube of 100×100×100 mm. The compressive strength of the concrete specimen corroded by sulfate after N dry-wet cycles is measured. The sulfate corrosion resistance coefficient K is recorded as the ratio of the compressive strength of the corroded specimen to the compressive strength of the original specimen.

[0059] (7) 28d anti-seepage pressure: The test is conducted in accordance with the Standard for Test Methods for Basic Properties of Building Mortar (JGJ / T70-2009). The maximum pressure of the formed concrete specimens is calculated based on the maximum pressure when no water seepage occurs in 4 of the 6 specimens in each group. The unit is MPa.

[0060] (8) Chloride ion permeability coefficient: Refer to the RCM method in the Standard for Long-term Performance and Durability Test Methods of Ordinary Concrete (GB / T50082) to test the permeability coefficient at different curing ages, accurate to 0.1*10 -12 m 2 / s.

[0061] Embodiment 1:

[0062] An induced film-forming concrete surface protective material comprises 15 parts of a mineralizer, 10 parts of a self-repairing capsule, 30 parts of an induction layer solution, and 20 parts of polydimethylsiloxane.

[0063] The mineralizer is a solution of Na2CO3, K2CO3, Na2SiO3, and K2SiO3 in a ratio of 1:1:1:1, and the ion concentration is 1.0 mol / L.

[0064] The induction layer solution is composed of metal enzyme and cationic solution, which are mixed in a mass ratio of 1:1.

[0065] The metalloenzyme is a mixture of tyrosinase, glutaminase and histidinase in a mass ratio of 1:1:1.

[0066] The cationic solution is a solution of calcium chloride, calcium acetate, calcium lactate, calcium bromide, magnesium chloride, magnesium bromide, and magnesium sulfate, with a ratio of 1:1:1:1:1:1:1:1, and an ion molar concentration of 1.0 mo / L.

[0067] The self-repairing capsules are made of chitosan as capsule wall material and polydimethylsiloxane as capsule core material, and are prepared into spherical particles with diameters of 0.75 mm and 1.18 mm through embedding.

[0068] The self-repairing capsules are prepared by an interfacial polycondensation method. By providing a two-phase interface, the capsule core and the capsule wall material undergo a polycondensation reaction, the capsule core is embedded in the capsule wall material, the aqueous solution of the capsule wall material and the capsule core material are mixed in a mass ratio of 1:1, and the pH is adjusted to 3.5; the mixed solution is transferred into a jacketed bottle, reacted at a constant temperature of 60°C, a speed of 300r / min, and the reaction is carried out for 2h. After the reaction is completed, it is filtered, the filter cake is washed with water, and dried at 40°C for 24h to obtain a self-repairing capsule.

[0069] A method for using an induced film-forming concrete protective material comprises the following steps:

[0070] S1. The anionic mineralizer is mixed with mixing water in advance, and the self-repairing capsule is mixed with cement, with the mass ratio of 0.1% and 1% of the cement mass respectively, prepared according to the C35 concrete mix ratio, and cement, sand, and crushed stone raw materials are added and mixed;

[0071] S2. After the concrete is poured and the formwork is set up and polished and cleaned, the 2Apply the induction layer solution and let it stand for more than 2 hours; pour the mixed concrete and vibrate it evenly;

[0072] S3. After pouring, let it stand for 24 hours, remove the formwork, and immediately apply 0.25kg / m 2 Spray polydimethylsiloxane material.

[0073] The test specimens were prepared and the test related properties were shown in the following table:

[0074] Table 1 Concrete surface protection material performance test

[0075] Test items unit Example 1 Expansion mm 350 Initial setting time min 180 3d compressive strength MPa 18 28d compressive strength MPa 37 Carbonization depth mm 0.2 Freeze-thaw cycle resistance - mass loss (cycles) % 0.2(2) 28d sulfate corrosion resistance coefficient % 99.9 365d sulfate corrosion resistance coefficient % 99.7 28d anti-seepage pressure MPa 2.0 56d Chloride ion permeability coefficient <![CDATA[m 2 / s]]> <![CDATA[0.2*10 -12 ]]> 365d Chloride ion permeability resistance coefficient <![CDATA[m 2 / s]]> <![CDATA[0.4*10 -12 ]]>

[0076] Embodiment 2:

[0077] An induced film-forming concrete surface protective material comprises 15 parts of anionic mineralizers, 10 parts of self-repairing capsules, 30 parts of induction layer solutions and 20 parts of polydimethylsiloxane.

[0078] The anion mineralizer is a solution of Na2CO3 and Na2SiO3 in a ratio of 1:1 and an ion concentration of 2.0 mol / L.

[0079] The induction layer solution is composed of metal enzyme and cationic solution, which are mixed in a mass ratio of 1:1.

[0080] The metalloenzyme is a mixture of tyrosinase, glutaminase and histidinase in a mass ratio of 1:1:1.

[0081] The cationic solution is calcium chloride, calcium acetate, calcium lactate, and calcium bromide solution, the ratio of which is 1:1:1:1, and the ion molar concentration is 2.0 mol / L.

[0082] The self-repairing capsules are made of chitosan as capsule wall material and polydimethylsiloxane as capsule core material, and are prepared into spherical particles with diameters of 0.75 mm and 1.18 mm through embedding.

[0083] The self-repairing capsules are prepared by an interfacial polycondensation method. By providing a two-phase interface, the capsule core and the capsule wall material undergo a polycondensation reaction, the capsule core is embedded in the capsule wall material, the aqueous solution of the capsule wall material and the capsule core material are mixed in a mass ratio of 1:1, and the pH is adjusted to 3.5; the mixed solution is transferred into a jacketed bottle, reacted at a constant temperature of 60°C, a speed of 300r / min, and the reaction is carried out for 2h. After the reaction is completed, it is filtered, the filter cake is washed with water, and dried at 40°C for 24h to obtain a self-repairing capsule.

[0084] A method for using an induced film-forming concrete protective material comprises the following steps:

[0085] S1. The anionic mineralizer is mixed with mixing water in advance, and the self-repairing capsule is mixed with cement, with the mass ratio of 0.1% and 1% of the cement mass respectively, prepared according to the C35 concrete mix ratio, and cement, sand, and crushed stone raw materials are added and mixed;

[0086] S2. After the formwork is set up for concrete pouring and cleaned, the 2 Apply the induction layer solution and let it stand for more than 2 hours; pour the mixed concrete and vibrate it evenly.

[0087] S3. After pouring, let it stand for 24 hours, remove the formwork, and immediately apply 0.25kg / m 2 Spray polydimethylsiloxane material.

[0088] The test specimens were prepared and the test related properties were shown in the following table:

[0089] Table 2 Concrete surface protection material performance test

[0090]

[0091]

[0092] By adjusting the molar concentrations of anions and cations, mineralized layers of different thicknesses can be formed according to the specimen, actual concrete thickness and site needs. This can be reflected on the specimen as different carbonization depths, improved resistance to sulfate erosion and resistance to chloride ion penetration, and can be used for concrete surface protection under marine engineering conditions.

[0093] Comparative Example 1:

[0094] The difference from Example 1 is that there is no matching concrete mixing, pouring, demolding and coating process, the surface protective material is added to the concrete, the proportion, preparation method, use method and other steps and the performance testing method are exactly the same, and the performance of the concrete prepared in Example 1 and Comparative Example 1 is compared.

[0095] Table 3 Concrete surface protection material performance test

[0096] Test items unit Example 1 Comparative Example 1 Expansion mm 350 200 Initial setting time min 180 300 3d compressive strength MPa 18 3 28d compressive strength MPa 37 15 Carbonization depth mm 0.2 5 Freeze-thaw cycle resistance - mass loss (cycles) % 0.2(2) 10 28d sulfate corrosion resistance coefficient % 99.9 60 365d sulfate corrosion resistance coefficient % 99.7 32 28d anti-seepage pressure MPa 2.0 0.01 56d Chloride ion permeability coefficient <![CDATA[m 2 / s]]> <![CDATA[0.2*10 -12 ]]> <![CDATA[5.0*10 -12 ]]> 365d Chloride ion permeability resistance coefficient <![CDATA[m 2 / s]]> <![CDATA[0.4*10 -12 ]]> <![CDATA[21.0*10 -12 ]]>

[0097] As can be seen from Table 4, there is a lack of matching concrete mixing, pouring, demolding and coating processes, and the mineralizing solution is directly put into the concrete. After the concrete is solidified and mixed, it affects the workability of the concrete and prolongs the hardening time of the concrete. It is impossible to form a mineralized layer on the surface, resulting in poor protective performance.

[0098] Comparative Example 2:

[0099] The difference from Example 1 is that the metal enzyme in the induction layer solution is missing, and the other components, proportions, steps such as usage methods and performance testing methods are exactly the same. The performance of the concrete prepared in Example 1 and Comparative Example 2 is compared.

[0100] Table 4 Concrete surface protection material performance test

[0101] Test items unit Example 1 Comparative Example 2 Expansion mm 350 350 Initial setting time min 180 170 3d compressive strength MPa 18 15 28d compressive strength MPa 37 36 Carbonization depth mm 0.2 2 Freeze-thaw cycle resistance - mass loss (cycles) % 0.2(2) 5 28d sulfate corrosion resistance coefficient % 99.9 86 365d sulfate corrosion resistance coefficient % 99.7 71 28d anti-seepage pressure MPa 2.0 0.5 56d Chloride ion permeability coefficient <![CDATA[m 2 / s]]> <![CDATA[0.2*10 -12 ]]> <![CDATA[1.0*10 -12 ]]> 365d Chloride ion permeability resistance coefficient <![CDATA[m 2 / s]]> <![CDATA[0.4*10 -12 ]]> <![CDATA[5.0*10 -12 ]]>

[0102] As can be seen from Table 5, in the absence of metal enzymes, the mineralizing solution undergoes very little mineralization on the surface of the concrete, forming a primary layer of protection, which has no effect on the workability and mechanical properties of the concrete; however, with the extension of the test time and the invasion of corrosive ions, the durability of the concrete protective layer decreases.

[0103] Comparative Example 3:

[0104] The difference from Example 1 is that the cationic solution in the induction layer solution is missing, and the other components, proportions, steps such as usage methods and performance testing methods are exactly the same. The performance of the concrete prepared in Example 1 and Comparative Example 3 is compared.

[0105] Table 5 Concrete surface protection material performance test

[0106]

[0107]

[0108] As shown in Table 6, the lack of cationic solution makes it impossible to form a surface mineralized layer protection, which will have no effect on the workability of concrete and the strength will be slightly weaker; however, as the test time increases and corrosive ions invade, the durability of the concrete protective layer decreases.

[0109] Comparative Example 4:

[0110] The difference from Example 1 is that the self-repairing capsule is missing, and the other components, proportions, usage methods and other steps as well as the performance testing method are exactly the same. The performance of the concrete prepared in Example 1 and Comparative Example 4 is compared.

[0111] Table 7 Concrete surface protection material performance test

[0112]

[0113]

[0114] As shown in Table 7, the lack of self-repairing capsules will not affect the workability and mechanical properties of concrete; however, with the extension of the test time (long age) and the invasion of corrosive ions, the durability of the concrete protective layer decreases.

[0115] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for protecting the surface of induced film-forming concrete, characterized in that: The steps are as follows: Add the mineralizer and self-repairing capsules into the concrete and mix them evenly for later use; Applying the induction layer solution on the template surface; Pour the mixed concrete into the formwork; Polydimethylsiloxane material is applied on the concrete surface after pouring.

2. The surface protection method of induced film-forming concrete according to claim 1, characterized in that: The induction layer solution is applied to the surface of the formwork before pouring concrete. The formwork is set up, polished and cleaned at a rate of 0.1-0.5 kg / m 2 Apply the induction layer solution and let it stand for more than 2 hours.

3. The method for protecting the surface of induced film-forming concrete according to claim 1, characterized in that: The polydimethylsiloxane material is applied to the concrete surface after pouring, which means that after pouring, the concrete surface is left to stand for 24 hours, the formwork is removed, and the polydimethylsiloxane material is applied to the concrete surface immediately at a rate of 0.1-0.2 kg / m 2 Spray polydimethylsiloxane material.

4. An induced film-forming concrete surface protective material, used in the induced film-forming concrete surface protective method according to any one of claims 1 to 3, characterized in that: The mass ratio of the mineralizer, the self-repairing capsule, the induction layer solution and the polydimethylsiloxane is 10-20:10-20:20-40:20-40.

5. The induced film-forming concrete surface protective material according to claim 4, characterized in that: The mineralizer contains CO3 2- and SiO3 2- A soluble salt solution with an ion molar concentration of 0.01 to 2.0 mol / L.

6. The induced film-forming concrete surface protective material according to claim 4, characterized in that: The self-repairing capsule is composed of a capsule wall material and a capsule core material, and is spherical in shape with a diameter of 0.75-1.18 mm.

7. The induced film-forming concrete surface protective material according to claim 6, characterized in that: The capsule wall material is chitosan molecules; the capsule core material is polydimethylsiloxane material.

8. The induced film-forming concrete surface protective material according to claim 4, characterized in that: The induction layer solution is prepared by mixing the metal enzyme and the cationic solution in a mass ratio of 1:

1.

9. The induced film-forming concrete surface protective material according to claim 8, characterized in that: The metal enzyme is one or a combination of tyrosinase, glutaminase and histidase.

10. The induced film-forming concrete surface protective material according to claim 8, characterized in that: The cation solution is Ca 2+ Mg 2+ Soluble salts have an ion molar concentration of 0.02 to 2.0 mol / L.